PENILAIAN PEMBELAJARAN TEMATIK DI MADRASAH - Akhmad Kunaini (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
Assessment is not only an inherent need but also plays a strategic role in the quality management of education. Good judgment will provide comprehensive evaluative information in a timely manner about the strengths and weaknesses of a learning activity or educational program. The assessment of thematic learning is an effort done to explore information gradually, continuously and holistic about the process and the result of growth and development that has been achieved, both related to the process and learning outcomes. However, most educators still experience constraints in assessing learning outcomes in the classroom, especially for teachers who implement thematic learning. In this case, educators have difficulty in applying techniques or syntax in the preparation of learning achievement instruments according to the condition of their students.